Landscape Anthropization Affects Mosquito Diversity in a Deciduous Forest in Southeastern Mexico. Issue 1 (3rd September 2021) - Barrientos-Roldán, Maggi Janelly; Abella-Medrano, Carlos Antonio; Ibáñez-Bernal, Sergio; Sandoval-Ruiz, César Antonio
Abstract: Mosquitoes (Diptera: Culicidae) are considered the group of insects that most impacts human health. Land use change, conversion of conserved sites into agricultural environments, urbanization, defaunation, and introduction of domestic animals can affect mosquito diversity positively or negatively, increasing the risk of transmission of zoonotic diseases. Here, we describe the diversity of adult mosquitoes in two environments (deciduous forest and anthropized zone) over 2 yr (2014–2016), using eight CDC traps at each site in three climatic seasons (rainy, cold, and dry). We captured 795 individuals belonging to 22 species. We constructed rank-abundance curves to determine spatial and temporal changes in the mosquito communities. We measured alpha diversity using the Shannon index (H′), Shannon exponential (e H ) and Simpson dominance (Ds), and beta diversity using Jaccard's coefficient of similarity (Ij). The most abundant species were Culex quinquefasciatus (40.5%), Culex coronator (18.3%), and Anopheles pseudopunctipennis (12.4%). The highest mosquito diversity was in the deciduous forest during the rainy season. Beta diversity analysis showed that species overlap varied among climatic seasons, with the sites sharing 65% species during the rainy season, but only 33% of species during the dry season. We found differences in the diversity of mosquitoes at the two sites, and the mosquito assemblage of the anthropized zone was significantly different from that of the deciduous forest.